“La Gestión administrativa de la Cooperativa de Ahorro y Crédito Acción y Desarrollo de la parroquia Licto, cantón Riobamba y su incidencia en la calidad de servicio durante el periodo 2015” - Caminos Moreno, Jessica Gabriela (2016)
This research project deals about the Gestión Administrativa de la Cooperativa de Ahorro y Crédito Acción y Desarrollo de la parroquia Licto, canton Riobamba and its impact on the quality of services during the period 2015. The study of administration applied to the Cooperative; It was of vital importance as it will allow the institution to reach the goals and objectives; these being, growth and efficient attention to partners; the same that is focused on achieving a privileged position in the local market, through efficiency and effectiveness in the administration and quality of service This research is constituted by five chapters; they developed the same as follows: Chapter I, in this chapter the reference framework is developed, which includes the planning and formulation of the problem, objectives and rationale of why and wherefore of this investigation, unit I data consisting of credit union savings and loan and Development Action Licto parish Chapter II, Theoretical Framework, it is divided in three units; the unit II covers and comprises everything related to the Administrative Management Unit III refers to the quality of service. Chapter III, the methods used for research, population and sample, operationalization of variables, techniques and tools for data collection, data processing, analysis and interpretation of results and hypothesis testing are detailed.